Improved Unity Magnitude Input Shaping Scheme For Sway Control Of An Underactuated 3D Overhead Crane With Hoisting - M.J.Maghsoudi; Liyana Ramli; S.Sudin; Z.Mohamed; A.R.Husain; H.Wahid (Elsevier, 2024)
Mechanical Systems and Signal Processing Volume 123, 15 May 2019, Pages 466-482